Basin-scale fluid-flow models of the McArthur River mineral system: constraints from geochemistry, geophysics and sequence stratigraphy. Issue 1 (1st December 2019) - Schaubs, Peter; Sheldon, Heather; Blaikie, Teagan; Kunzmann, Marcus; Schmid, Susanne; Spinks, Sam
Summary: This abstract reports on the insights gained from numerical simulations which have been used to place constraints on the nature of critical geological processes responsible for sediment-hosted base metal mineralisation in the southern McArthur Basin, Australia. The study was undertaken as part of a multidisciplinary study which also included the interpretation of new and existing geophysical datasets; detailed sedimentological and stratigraphic analysis; petrography; geochemistry; and the basin-scale numerical modelling of fluid flow described here. The integration of information from this multidisciplinary study has been used to refine and constrain these coupled 3D deformation – heat transport – fluid flow simulations to determine 1) the relative effects of deformation and heat transport (convection) in driving fluid flow, 2) how extensional versus contractional deformation effects fluid flow direction within faults and 3) conditions conducive for syngenetic vs diagenetic mineralisation. Numerical models suggest that the convective flow (and potential mineralisation) would have continued during extensional deformation, unless the deformation occurred at an extremely high strain rate, while contractional deformation would have enhanced the upward convective flow. These results indicate that it is not necessary to invoke inversion to explain upward flow of mineralising fluids in this system, although an inversion event may have enhanced mineralisation in areas of convective upwelling. Geochemistry and petrography support a diagenetic origin for the mineralisation, implying low permeability at the top of the Emu Fault which is consistent with stratigraphic and sedimentological analysis of the Barney Creek Formation. Numerical modelling confirms that such a permeability scenario would result in upwelling fluids being diverted out of the Emu Fault into the Barney Creek Formation.